Assessing graduate employability in the faculty of natural sciences at Mangosuthu University of Technology: A mixed-methods cross-sectional study on challenges and solutions. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background Graduate unemployment remains a significant concern in South Africa, particularly in science-related fields where misalignment between academic training and labour market expectations persists. At Mangosuthu University of Technology (MUT), the Faculty of Natural Sciences produces graduates in various disciplines; however, many encounter challenges transitioning into employment. This study assesses the employability of these graduates, identifies employment barriers, and proposes institutional strategies to enhance career readiness. Methods A mixed-methods cross-sectional design was used. Quantitative data were gathered via structured questionnaires from 120 recent graduates across multiple disciplines. Qualitative insights were obtained through semi-structured interviews with 10 academic staff and 5 industry employers. The study explored graduates’ perceptions of readiness, skill alignment with market needs, and employment outcomes. Data were analysed using descriptive statistics, thematic analysis, and triangulation. Results Only 38% of graduates secured employment within 12 months post-graduation. Key barriers included limited work-integrated learning, insufficient practical experience, and poor industry exposure. Employers reported deficiencies in communication, problem-solving, and digital competencies. Academic staff highlighted the need for curriculum reform and stronger industry collaboration. A clear disconnect between academic preparation and employability expectations emerged. Conclusion Graduate employability challenges in the Faculty of Natural Sciences are linked to structural gaps in the curriculum and limited experiential learning. While graduates possess core scientific knowledge, their employability is constrained by inadequate workplace exposure and soft skills. Recommendations MUT should enhance work-integrated learning, introduce industry-driven short courses, incorporate soft skills into the curriculum, and foster formal partnerships with employers. These interventions will better align education with industry needs, improving graduate employability and institutional impact.